Winning with adhd ebook A playbook for teens and young adults with attention deficit/hyperactivity disorder. - Friedman, Grace (Instant Help Solutions., 2019)
Get the real inside scoop on thriving as a teen with attention deficit/hyperactivity disorder (ADHD). Drawing on her own experiences living with the disorder, college student Grace Friedman—along with pediatric neurologist Sarah Cheyette—offers valuable tips and tricks to help you face the unique challenges of ADHD. If you're a teen with ADHD, you care about academic and social success just as much as your peers do, but you may also experience difficulties keeping up in school and maintaining good relationships with friends and family. In addition, you probably find it challenging to stay organized, articulate your struggles to others, and cope with overwhelming pressure—especially as college approaches. This workbook will give you solid skills for addressing the challenges of ADHD so you can live up to your true potential. In Winning with ADHD , you'll learn powerful and proven-effective cognitive behavioral strategies for coping with overwhelm, staying organized, tackling assignments, preparing for exams, dealing with emotions, communicating effectively with adults, and maintaining strong friendships. You'll also find valuable information about ADHD medication, how your brain works, as well as self-advocacy skills to help you get ahead in high school, college, and beyond. As a teen with ADHD, you may face many unique challenges. This workbook will give you everything you need to get one step ahead of your ADHD and thrive in all aspects of life.